(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Fruit wastes and their byproducts may cause serious environmental problems, since it accumulates in agro-industrial yards without having any significant and commercial value. Pineapple(Family - Bromeliaceae) is one of the leading edible tropical fruit produced in the world. Pineapple peel is the massive waste produced by the pineapple processing industry leading to environmental pollution. In this regard, efforts have been made in order to tap the potential of this bio-waste as source of bioactive compounds by isolating, purifying and characterizing known as well as novel secondary metabolites from it and can be used for studying its application in various industries. A phenolic compound namely Ferulic acid is isolated from this bio-waste and its structure has been elucidated by Fourier Transform Infrared (FT-IR) spectroscopy, Liquid Chromatography-Mass Spectrometry (LC-MS), High Performance Liquid Chromatography (HPLC), 1H NMR and 13C Nuclear Magnetic Resonance (NMR) spectra. The anti-inflammatory potential of Ferulic acid was studied in vitro on Lipopolysaccharide (LPS) stimulated Ralph and Williams (RAW) and Tamm-Horsefall Protein-1 (THP-1) cell lines. The levels of pro-inflammatory enzymes such as cyclooxygenase (COX), lipooxygenase (LOX), and myeloperoxidase (MPOX) activities on THP-1 cell lines and the tested compound, exhibited a dose-dependent anti-inflammatory activity. Ferulic acid showed remarkable activity by COX (78.47%) and LOX (78.63%) inhibition in LPS stimulated THP-1 cells at 100 μg/mL. Different concentrations of Ferulic Acid (FER) effectively decreased the MPOX (92.76℅) level in a dose dependent manner and the results were comparable to standard drug Indomethacin. The isolated phenolic compound, ferulic acid, effectively lowered inflammatory cytokines like Tumour Necrosis Factor Alpha (TNF-α), Interleukin-6 (IL-6) and Interleukin-1 Beta (IL-1β) along with prostaglandin E2 and leukotriene C4 and cellular nitrate levels in LPS stimulated RAW cells.